2022
DOI: 10.1098/rspb.2022.0868
|View full text |Cite
|
Sign up to set email alerts
|

Stressors interact across generations to influence offspring telomeres and survival

Abstract: Parental stress often has long-term consequences for offspring. However, the mechanisms underlying these effects and how they are shaped by conditions offspring subsequently experience are poorly understood. Telomeres, which often shorten in response to stress and predict longevity, may contribute to, and/or reflect these cross-generational effects. Traditionally, parental stress is expected to have negative effects on offspring telomeres, but experimental studies in captive animals suggest that these effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 57 publications
1
23
0
Order By: Relevance
“…We identi ed one individual (a female from the Hestmannøy population) that showed signi cant consistent telomere elongation throughout life at a greater rate than might have been expected by measurement error (see Supporting Information). Recent studies on house sparrows in other populations have also showed instances of telomere lengthening within some individuals [84,103] and that house sparrows may experience rather transient TL shortening in response to stressors [104]. However, TL also generally declined with age in another long-term study of house sparrows [18,84].…”
Section: Discussionmentioning
confidence: 98%
“…We identi ed one individual (a female from the Hestmannøy population) that showed signi cant consistent telomere elongation throughout life at a greater rate than might have been expected by measurement error (see Supporting Information). Recent studies on house sparrows in other populations have also showed instances of telomere lengthening within some individuals [84,103] and that house sparrows may experience rather transient TL shortening in response to stressors [104]. However, TL also generally declined with age in another long-term study of house sparrows [18,84].…”
Section: Discussionmentioning
confidence: 98%
“…We identified one individual (a female from the Hestmannøy population) that showed significant consistent telomere elongation throughout life at a greater rate than might have been expected by measurement error (see Supporting Information). Recent studies on house sparrows in other populations have also showed instances of telomere lengthening within some individuals 90,112 and that house sparrows may experience rather transient TL shortening in response to stressors 113 . However, TL also generally declined with age in another long-term study of house sparrows 22,90 .…”
Section: Discussionmentioning
confidence: 99%
“…Any stress experienced by parents may also affect the telomere dynamics (i.e. telomere length and rate of loss) of the next generation via genetic and/or parental effects pathways ( Tarry-Adkins et al, 2009 ; Asghar et al, 2015 ; Marasco et al, 2019 ; Young et al, 2022 ), which in turn may depend on offspring sex ( Marasco et al, 2019 ) and/or offspring environment ( Young et al, 2022 ). While the estimation of telomere heritability is complicated by the fact that telomere lengths change through life and are under the influence of extrinsic factors, a recent meta-analysis reported an average heritability score of ~ 45% ( Chik et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%